In vitro activity of a partially purified and characterized bark extract of Castanea sativa Mill. (ENC®) against Chlamydia spp. (4th March 2017) - Papa, Valentina; Ginocchietti, Laura; Budriesi, Roberta; Micucci, Matteo; Costa, Roberta; Biondi, Roberta; Cevenini, Roberto; Chiarini, Alberto; Aldini, Rita; Donati, Manuela; Pollini, Gian Matteo; Cenacchi, Giovanna
ABSTRACT: Castanea sativa Mill (ENC®), containing tannins against 33 Chlamydia strains, was compared to SMAP-29 with inhibitory effect against C. trachomatis and C. pneumoniae . The ENC® activity against Chlamydia spp. was evaluated determining the lowest concentration to achieve more than half reduction of intact chlamydial inclusions versus controls. ENC® reduced all Chlamydia strains tested at 1 µg/mL, while SMAP-29 induced reductions of C. trachomatis and C. pneumoniae infectivity at 10 µg/mL. A great reduction of C. trachomatis, C. pneumoniae, and C. abortus infectivity was achieved with a 10 µg/mL ENC® concentration, whereas their infectivity was almost inhibited at 100 µg/mL ENC® concentration.